Culture of time and space, 1880-1918 - Kern, Stephen (London, 1983)
Stephen Kern writes about the sweeping changes in technology and culture between 1880 and World War I that created new modes of understanding and experiencing time and space. To mark the book$1 (Bs twentieth anniversary, Kern provides an illuminating new preface about the breakthrough in interpretive approach that has made this a seminal work in interdisciplinary studies.s
Keywords: Social change